Corneal Endothelial Cell Loss in Glaucoma Treatment Procedures: A Brief Review - Yadgari, Maryam; Shahriari , Mansoor (Journal of Ophthalmic and Optometric Sciences, 2020)
Abstract Glaucoma surgeons should be careful about damage to the corneal endothelial cells during glaucoma surgeries particularly during glaucoma drainage device implantation. The patients should be monitored for possible corneal decompensation. Also shunt procedures should be performed with a wider tube corneal angle to avoid possible endothelial cell damage. Here we briefly review corneal endothelial cell loss in different glaucoma treatment methods. Keywords: Cornea; Endothelial Cell Loss; Glaucoma; Review.